Analisis Penggunaan HOTS Di Soal Asesmen Sumatif Mata Pelajaran Bahasa Jawa - Sulistyawati, Heni; Wulan, Sri Hertanti; Hesti Mulyani (Piwulang Jurnal Pendidikan Bahasa Jawa, 2025)
The background of this study is based on the importance of improving the quality of learning in line with the demands of the 21st century, particularly in fostering critical thinking and problem-solving skills. This study aims to explain the use of Higher Order Thinking Skills (HOTS)-based questions in the summative assessments ASAT (Javanese Language) for the 2022/2023 academic year and ASAS (Javanese Language) for the 2023/2024 academic year, as well as to compare the percentage of HOTS questions between the two. This type of research uses a qualitative approach with data sources consisting of ASAT and ASAS question sheets, analyzed using an interactive model involving data collection, data condensation, data display, and drawing conclusions. The research data consists of multiple-choice and essay items. The results show that in both assessments, there are still some questions that do not fully meet HOTS criteria, and there are inaccuracies in the selection of Operational Verbs (KKO). However, in general, the stimuli used are educational, varied, inspiring, and contextual. The percentage of question levels shows that in ASAT, the distribution is 20% LOTS, 35.56% MOTS, and 44.44% HOTS; whereas in ASAS, the distribution is 8% LOTS, 38% MOTS, and 54% HOTS. The conclusion of this study is that the ASAS summative assessment questions show a higher tendency to implement HOTS-based questions compared to ASAT.